2019
DOI: 10.1016/j.stueduc.2019.03.008
|View full text |Cite
|
Sign up to set email alerts
|

More knowledge helps implement change: Evaluation of a training program during educational reform

Abstract: or through my researchgate.net account. 2 More knowledge helps implement change: Evaluation of a training program during educational reform

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…First, the data generated by the evaluation of the training support the decision-making process that allows adjusting the interventions, extending them, cutting them or replacing them. In addition, the evaluation is used to verify that training contributes to improving the training system, to skills development, and to knowing whether training has influenced performance (Zala-Mezö et al, 2019). The second way is through the reactions of those trained because satisfaction is considered an element that significantly affects training transfer (Colquitt et al, 2000).…”
Section: Training Evaluation and Training Needs Analysis Training App...mentioning
confidence: 99%
See 1 more Smart Citation
“…First, the data generated by the evaluation of the training support the decision-making process that allows adjusting the interventions, extending them, cutting them or replacing them. In addition, the evaluation is used to verify that training contributes to improving the training system, to skills development, and to knowing whether training has influenced performance (Zala-Mezö et al, 2019). The second way is through the reactions of those trained because satisfaction is considered an element that significantly affects training transfer (Colquitt et al, 2000).…”
Section: Training Evaluation and Training Needs Analysis Training App...mentioning
confidence: 99%
“…It has been proven that the implementation of the training and the support of the application have a positive relationship with the transfer of training and that the evaluation of the training mediates EJTD 46,5/6 this relationship. These results have two practical implications: the first, the importance of managers' and department heads' support for the transfer of training and the second, the importance of implementing training evaluation processes in schools as evaluation is linked to training transfer (Zala-Mezö et al, 2019). The critical idea is to create learning environments, which support formal learning and self-learning, and informal learning in the workplace (Baldwin et al, 2017).…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Education quality evaluation has amassed a lot of data as a key component of learning and teaching. e data conceals a wealth of laws and issues that must be uncovered and applied immediately [9]. One important area of data research is how to use big data responsibly to support decision-making for the advancement of all spheres of life.…”
Section: Introductionmentioning
confidence: 99%
“…pre-service TSE in combining NS knowledge in their pedagogical methods will significantly explain the variance in attitudes towards change (combining knowledge from NS research in education), was refuted in this study. This finding was surprising in regards to previous studies, since according to the literature, teachers' high or low efficacy may influence levels of change's implementation (Stanton, Cawthon, & Dawson, 2018), and that change-related self-efficacy proved to be a solid predictor for positive attitudes and behavior in organizational changes (Zala-Mezö, Raeder, & Strauss, 2019).) In their study from 2013, a number of 700 elementary school teachers were surveyed; the data indicated a positive association between self-efficacy and attitudes toward change.…”
Section: Discussionmentioning
confidence: 78%